Association of brain copper with cognitive decline in a community‐based neuropathologic study: Human neuropathology/other. (7th December 2020) - Agarwal, Puja; Dhana, Klodian; Schneider, Julie A.; Ayton, Scott; Wang, Yamin; Agrawal, Sonal; Bennett, David A.; Barnes, Lisa L.; Leurgans, Sue E.; Bush, Ashley I.; Morris, Martha Clare
Abstract: Background: Copper (Cu) is an essential metal for brain health. Limited studies reported no association of plasma Cu and inverse association of Cu in human hair with cognitive abilities in older adults. However, no study investigated the association of Cu levels in the human brain with the long‐term change in cognitive functioning before death. Thus, we aim to examine the association of brain Cu with cognitive decline in a community‐based cohort study. Method: Using data from 625 deceased participants from the Rush Memory and Aging Project. Brain copper levels were measured using ICP‐MS in gray matter from inferior temporal, mid frontal, anterior cingulate, and cerebellum. Composite global cognition and specific domains were derived from z‐scores of a 19‐panel cognitive tests that were performed annually for up to 14 years proximate to death. We used linear mixed‐effects models to examine associations of Cu (grouped in tertiles) in the brain with cognitive decline. All the models were controlled for age at death, sex, education, late‐life cognitive activity, physical activity, smoking, and APOE‐ɛ4 status. Result: The mean age at first cognitive assessment was 82.7 (±5.8) years, 71% were women, and 25% carried an APOE‐ɛ4 allele. Participants in the highest and the middle tertile of Brain Cu in the inferior temporal region had a slower annual rate of cognitive decline (T3 vs. T1:β= 0.027; T2 vs. T1: β= 0.032; p for trend= 0.007). Similar associations were found for specific domains, including episodic memory (T3 vs. T1: β= 0.027; T2 vs. T1: β= 0.033; p for trend= 0.03), semantic memory ((T3 vs. T1:β= 0.040; T2 vs. T1: β= 0.050; p for trend= 0.001) and perceptual speed (T3 vs. T1:β= 0.024; T2 vs. T1: β= 0.035; p for trend= 0.03). Concentrations of Cu in the other brain regions were not associated with cognitive decline. Conclusion: The association of higher brain copper levels in the vulnerable region of Alzheimer's disease, such as the inferior temporal region with slower cognitive decline, supports the role of copper dyshomeostasis in the disease process.